When is a Voluntary Code Not Voluntary? - Mak, Yuen Teen (Institutional Knowledge at Singapore Management University, 2008)
Many countries have adopted the ‘comply or explain’ approach to raise standards of corporate governance in listed companies. The approach has now found its way into the charity sector in Singapore. Mak Yuen Teen highlights some misconceptions about the voluntary nature of the approach and provides suggestions for its effective implementation.